The association between walking pace and grip strength and all-cause mortality: A prospective analysis from the MAUCO cohort. (February 2023) - Petermann-Rocha, Fanny; Parra-Soto, Solange; Cid, Vicente; Venegas, Pia; Huidobro, Andrea; Ferreccio, Catterina; Celis-Morales, Carlos
Highlights: Grip strength and walking pace are simple tests for clinical and research use and have a good predictive ability to identify people at higher risk of mortality. Slow walking pace and low grip strength – investigated both in isolation and in combination – were associated with a higher risk of all-cause mortality in Chilean adults even after adjusting for a wide range of potential confounding factors. The results highlight the relevance and implications of assessment of these markers. Abstract: Objective: This study investigated the individual and combined association of walking pace and grip strength with all-cause mortality in Chilean adults. Study design: 8813 participants (54.6 % women) from the MAUCO population-based cohort were included in this prospective study. Main outcome measures: Individual and combined associations of grip strength (normal or low grip) and walking pace (normal or slow walking) with all-cause mortality were investigated using Cox proportional-hazard models. Analyses were adjusted for sociodemographic, lifestyle, and health-related factors. Results: Over a median follow-up of 4.74 years, 151 and 206 participants included in the analyses of walking pace and grip strength died. Individuals with low grip strength had a risk of dying 2.40 times (95 % CI: 1.64 to 3.51) higher than their counterparts with normal grip strength. Similar results were identified for slow walkers (HR: 1.77 [95 % CI: 1.25 to 2.50]). When the two factors were combined and the associations investigated, individuals with normal walking pace but with low grip strength had a higher risk of all-cause mortality than those with normal walking pace and normal grip strength (HR: 3.56 [95 % CI: 1.99 to 6.36]). The associations remained even after including a 1- and 2-year landmark period in the analyses. Conclusions: Slow walking pace and low grip strength were associated with a higher risk of mortality (both in isolation and combined). These factors might be early markers of all-cause mortality, and should be measured more frequently in middle-aged and older adults in clinical practice.